Experiences in Finding and Using OER in Teacher Education Programmes: Pedagogical Approach and Challenges - Philips, John Arul (Commonwealth of Learning, 2012)
This chapter discusses the author’s experience of using web resources — both open educational resources (OER) and non-OER — in undergraduate and graduate teacher education programmes. The focus is on the pedagogical and learning principles guiding the selection, sequencing and organisation of web resources in supporting programmes that use a blended learning approach. Specific examples are provided to illustrate how the pedagogical principles are applied in the use of web resources for supporting learning. Emphasis is on the changing role of teachers in higher education institutions, who will become content curators, and on engaging students in higherorder thinking. Finally, several challenges that may determine the future of using such resources for teaching and learning with OER and non-OER are discussed.